Kemampuan Bandara Sultan Hasanuddin Makassar Menghadapi Pengoperasian Pesawat Udara Super Jumbo A-380 - M. N. Nurrasmajid (WARTA ARDHIA, 2010)
Aviation technologi develops increasingly sophisticated marked by producing of super jumbo aircraft Airbus A-380. This aircraft has four engines made by Rolls-Trent Royce-90 is capable to provide 36.280 Kg of thrust or four turbo-fan engine Alliance HP 7200 with 37 003 Kg of frust with passenger capacity up to 850 passengers. In the world, aviation business world today around 15 airlines have ordered the aircraft (total 154 order), such as Emirates, Lufthansa, Qantas, Singapore Airlines, dan Malaysia Airlines.In order to anticipate the development of aviation technologi, Idonesian government have to prepare airport in Indonesia that could be landed by super jumbo aircraft Airbus A-380. For the case, it needs to conduct the study on the readiness of Sultan Hasanuddin Airport in Makasar for the operation Of the super jumbo aircraft Airbus A-380. The evaluation of readiness for area, air side and land side facilities including the support facilities that might be developed to accommodate the aircraft Airbus A-380.